Orbital Floor Blow-Out Fractures: Ultrasonography, Postoperative Complications and Rehabilitation (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2012)
The aim of this retrospective study was to analyze indications and the efficiency of post-operative rehabilitation in patients with orbital floor blow-out fractures. The selected patients were with orbital floor blow-out fractures and post-operative rehabilitation; eight case records were traced. The symptoms of the eyes (eye position and movements, coordimetry, ultrasonography) were noted before and after surgical correction and rehabilitation treatment. The data were statistically analyzed using a computer software package, SPSS version 16.0. A value of p < 0.05 was considered as statistically significant. All eight (100%) patients were men. The average age was 19.88 ± 8.25 years (14–34 years). The most common complaint was diplopia, it was in eight (100%) patients’ numb of affected face side was in two (28.6%), vertigo in one (12.5%), nausea in one (12.5%) patient. Post–operative complications were: diplopia – eight (100%) patients, postoperative scar – three (37.5%), eyelid swelling – four (50%), haematoma – one (12.5%) patient. After rehabilitation post-operative symptoms (postoperative scar, eyelid swelling, haematoma) decreased significantly (p < 0.05). Insignificant diplopia was left in seven (87.5%) (p > 0.05) patients, but it did not disturb their general activities. Patients were not treated surgically, neither they got correction with prismatic spectacles after rehabilitation. One (12.5%) patient was under supervision. Before rehabilitation ultrasonography was done for five (62.5%) patients. Ultrasonography was repeated only for one (12.5%) patient after rehabilitation. Coordimetry was done for all patients while they were being treated in order to find out the efficiency of rehabilitation. Rehabilitation can be recommended to patients with post-operative complications such as diplopia, swelling, post-operative scar. Treatment effect should be objectified by ultrasonography.Keywords: rehabilitation, orbital floor fracture, postoperative complications, ultrasonography.